Urban Planning in the Era of Global Uncertainty: Addressing Emerging Challenges and Systemic Risks - Abubakar Isyaku Ismail (Analitika: Journal of Management and Finance, 2026)
Purpose: This paper aims to examine how urban planning responds to pressing contemporary global challenges, including rapid urbanization, climate change, housing shortages, and social inequality. It seeks to identify strategic approaches that enhance sustainability, resilience, and inclusivity in urban development. Design/methodology/approach: The study adopts a qualitative review approach by synthesizing recent scholarly literature and selected international case studies on urban planning practices. Through comparative and thematic analysis, the paper evaluates current planning strategies and emerging policy frameworks addressing global urban issues. Findings: The findings indicate that integrated planning approaches—combining sustainability principles, climate resilience strategies, and inclusive governance mechanisms—are critical for managing complex urban challenges. Innovative models such as adaptive urban design, participatory planning, and data-driven governance enhance cities’ capacity to respond to environmental and socio-economic uncertainties. Research implications: This study contributes to contemporary urban planning discourse by emphasizing the need for multidimensional and adaptive planning frameworks. The findings provide theoretical insights for scholars and practical guidance for policymakers seeking to develop future-ready and resilient cities in an era of global transformation.